Expression analysis of MND1/GAJ, SPATA22, GAPDHS and ACR genes in testicular biopsies from non-obstructive azoospermia (NOA) patients - Dorosh, Andriy; Tepla, Olina; Zatecka, Eva; Ded, Lukas; Koci, Karel; Peknicova, Jana (Reproductive biology and endocrinology, 2013)
BACKGROUND: High-throughput studies provide a wide spectrum of genes for use as predictive markers during testicular sperm extraction (TESE) in combination with ICSI. In this work, we used the specimens from testicular biopsies of men with non-obstructive azoospermia who underwent TESE to investigate the expression of spermatogenesis-related genes MND1, SPATA22, GAPDHS and ACR. METHODS: Testicular biopsy specimens were subdivided into three groups: hypospermatogenesis (HS); maturation arrest (MA); and Sertoli cell-only syndrome (SCO). The levels of expression of the spermatogenesis-related genes MND1, SPATA22, GAPDHS and ACR in the testes were compared among these three groups using the reverse transcription polymerase chain reaction (RT-PCR) technique. RESULTS: Analysis of the expression of spermatogenic genes in human testes with abnormal spermatogenesis showed different expression patterns in patients from different groups. Fertilization rate for studied set of patients was 66% and pregnancy rate 29%. For HS group fertilization rate was 72% and pregnancy rate 32%, while for MA group fertilization and pregnancy rates were 54% and 26%, respectively. Fertilization rates in relation to the studied genes were uniformly around 70%, pregnancy rates for ACR and GAPDHS genes were surprisingly low at 6% and 8% correspondingly. CONCLUSIONS: Analysis of the expression of genes involved in spermatogenesis can be a fast additional test for the level of spermatogenesis in testicular samples.
Keywords: Sperm Retrieval; Male; Middle Aged; akrosin; Sertoli Cell-Only Syndrome; oligospermie; Fertilization; spermatogeneze; Pregnancy Rate; nemoci varlat; Pregnancy; těhotenství; Adult; biopsie; Azoospermia; dospělí; glyceraldehyd-3-fosfátdehydrogenasy; mužské pohlaví; Sperm Injections, Intracytoplasmic; Spermatogenesis; Testis; polymerázová řetězová reakce s reverzní transkripcí; stanovení celkové genové exprese; Testicular Diseases; Gene Expression Profiling; proteiny buněčného cyklu; lidé; Glyceraldehyde-3-Phosphate Dehydrogenases; ženské pohlaví; Humans; úhrn těhotenství na počet žen v reprodukčním věku; testis; intracytoplazmatické injekce spermie; Oligospermia; Reverse Transcriptase Polymerase Chain Reaction; odběr spermií; Biopsy; azoospermie; Acrosin; Female; Cell Cycle Proteins; lidé středního věku; Sertoli cell only syndrom; fertilizace